2019
DOI: 10.3390/v11060521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rhinovirus Infections in Children

Abstract: Rhinovirus (RV) is an RNA virus that causes more than 50% of upper respiratory tract infections in humans worldwide. Together with Respiratory Syncytial Virus, RV is one of the leading causes of viral bronchiolitis in infants and the most common virus associated with wheezing in children aged between one and two years. Because of its tremendous genetic diversity (>150 serotypes), the recurrence of RV infections each year is quite typical. Furthermore, because of its broad clinical spectrum, the clinical var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 91 publications
4
49
0
1
Order By: Relevance
“…It has been observed that the composition and abundance of the URT and LRT virome differs among healthy subjects and asymptomatic and symptomatic patients with chronic respiratory diseases, but detailed longitudinal studies are needed for better comprehension of the causal relationships (Sundell et al, 2019;Freer et al, 2018). Complex interactions between viruses and additional environmental and intrinsic factors are probably responsible for the longer but transient presence of some viruses in the respiratory tract of asthmatic patients or the development of fully blown infections leading to severe exacerbations (Vandini et al, 2019;Sarna et al, 2018).…”
Section: Virions Readily Colonize the Lungsmentioning
confidence: 99%
“…It has been observed that the composition and abundance of the URT and LRT virome differs among healthy subjects and asymptomatic and symptomatic patients with chronic respiratory diseases, but detailed longitudinal studies are needed for better comprehension of the causal relationships (Sundell et al, 2019;Freer et al, 2018). Complex interactions between viruses and additional environmental and intrinsic factors are probably responsible for the longer but transient presence of some viruses in the respiratory tract of asthmatic patients or the development of fully blown infections leading to severe exacerbations (Vandini et al, 2019;Sarna et al, 2018).…”
Section: Virions Readily Colonize the Lungsmentioning
confidence: 99%
“…The great heterogeneity of these results may be due to the differences between the described researches, such as study design, sample size, and considered outcomes, but also may be partially related to the fact that RV is a very ubiquitous virus. Its prevalence among asymptomatic children has been reported up to 40% [ 38 ], and its detection in nasal specimens, together with other viruses during acute bronchiolitis, may lead to giving RV a causative role that it possibly does not always have [ 39 ].…”
Section: Rhinovirus Infection and Bronchiolitis Severitymentioning
confidence: 99%
“…However, it alters the epithelial barrier’s function, dissociating the zonula occludens-1 from tight junction complex through the release of reactive oxygen species during viral replication [ 50 ]. This alteration can allow the absorption of higher amounts of aeroallergens, strictly related to the development of wheezing and asthma [ 39 ]. Moreover, different RV types use several specific vehicles to enter into airway epithelium: RV-A and -B types use ICAM-1 or the low-density lipoprotein receptor (LDL-R), while recently, the cadherin-related family member 3 has been identified as a receptor for RV-C [ 36 , 39 ].…”
Section: Long-term Sequelae Of Rv Bronchiolitismentioning
confidence: 99%
See 2 more Smart Citations